Total burden of hepatitis B and C attributed to injecting drug use in 204 countries and territories from 1990 to 2021: Analyses based on the Global Burden of Disease Study 2021 - Liang Huang; Xiaoyu Chen; Zhaojun Wang (International Journal of Infectious Diseases)
Objectives: This study assesses the global, regional, and national burden of hepatitis B virus (HBV) and hepatitis C virus (HCV) related to injecting drug use (IDU) from 1990 to 2021. Methods: Data from the Global Burden of Disease Study 2021 were analyzed to quantify deaths, age-standardized mortality rates (ASMR), disability-adjusted life years (DALYs), and age-standardized DALYs rates (ASDR) due to HBV and HCV from IDU across 204 countries. Trends were evaluated using estimated annual percentage change. Analyzing the association between ASDR and SDI using a loess regression model. Results: From 1990 to 2021, the global burden of deaths and DALYs due to HBV and HCV attributed to IDU showed an increasing trend, especially among males, whose mortality rates were significantly higher than females. In 2021, global deaths due to HBV from IDU were 13,050.8, with an ASMR of 0.15 per 100,000 and an ASDR of 5.3, both showing an increasing trend with estimated annual percentage changes (EAPCs) of 1.09 and 0.96, respectively. HCV deaths reached 231,764.4, with an ASMR of 2.68 (EAPC: 0.38) and a relatively stable ASDR trend (EAPC: 0.01). Although raw death rates for HCV have increased, the ASMR and ASDR have remained stable or slightly declined, highlighting different trends across sexes and regions. India had the highest national deaths, while the highest ASDRs were in the Republic of Moldova (HBV) and Mongolia (HCV). South Asia recorded the highest regional deaths for both HBV and HCV. Positive correlations between ASDRs for HBV and HCV with SDI were observed. Conclusion: The burden of HBV and HCV due to IDU has increased from 1990 to 2021, especially among males, with significant regional and national disparities. Targeted drug prohibition interventions and policies are needed.